The Molecular Cloud Life Cycle. I. Constraining H2 Formation and Dissociation Rates with Observations - Shmuel Bialy; Blakesley Burkhart; Daniel Seifried; Amiel Sternberg; Benjamin Godard; Mark R. Krumholz; Stefanie Walch; Erika Hamden; Thomas J. Haworth; Neal J. Turner; Min-Young Lee; Shuo Kong (The Astrophysical Journal)
Molecular clouds (MCs) are the birthplaces of new stars in galaxies. A key component of MCs are photodissociation regions (PDRs), where far-ultraviolet radiation plays a crucial role in determining the gas’s physical and chemical state. Traditional PDR models assume a chemical steady state (CSS), where the rates of H _2 formation and photodissociation are balanced. However, real MCs are dynamic and can be out of CSS. In this study, we demonstrate that combining H _2 emission lines observed in the far-ultraviolet or infrared with column density observations can be used to derive the rates of H _2 formation and photodissociation. We derive analytical formulae that relate these rates to observable quantities, which we validate using synthetic H _2 line emission maps derived from the SILCC-Zoom hydrodynamical simulation. Our method estimates integrated H _2 formation and dissociation rates with an accuracy ≈30% (on top of the uncertainties in the observed H _2 emission maps and column densities). Our simulations, valid for column densities N ≤ 2 × 10 ^22 cm ^−2 , cover a wide dynamic range of H _2 formation and photodissociation rates, showing significant deviations from CSS, with 74% of the MC’s mass deviating from CSS by a factor greater than 2. Our analytical formulae can effectively distinguish between regions in and out of CSS. When applied to actual H _2 line observations, our method can assess the chemical states of MCs, providing insights into their evolutionary stages and lifetimes. A NASA Small Explorer mission concept, Eos, will be proposed in 2025 and is specifically designed to conduct the types of observations outlined in this study.